Impact of Hindu culture on Muslims - Madani, Mohsen Saeidi, 1957- (New Delhi : M D Publications, 1993)
Study based on two cities of Bihar, Patna and Ranchi.
Includes bibliographical references (p. [179]-181).
Keywords: Muslims -- India -- Patna -- Social life and customs -- Hindu influences; Muslims -- India -- Ranchi -- Social life and customs -- Hindu inlfuences; Hinduism -- Influence; Islam -- India -- Patna -- History; Islam -- India -- Ranchi -- History; Patna (India) -- Social life and customs; Ranchi (India) -- Social life and customs